B chromosomes are associated with redistribution of genetic recombination towards lower-recombination chromosomal regions in perennial ryegrass - Harper, John; Phillips, Dylan; Thomas, Ann; Gasior, Dagmara; Evans, Caron; Powell, Wayne; King, Julie; King, Ian; Jenkins, Glyn; Armstead, Ian (Oxford University Press, 2018)
Supernumerary ‘B’ chromosomes are non-essential components of the genome present in a range of plant and animal species – including many grasses. Within diploid and polyploid ryegrass and fescue species, including the forage grass perennial ryegrass (Lolium perenne L.), the presence of B chromosomes has been reported as influencing both chromosome pairing and chiasma frequencies. In this study, the effects of the presence/absence of B chromosomes on genetic recombination has been investigated through generating DArT marker genetic maps for 6 perennial ryegrass diploid populations, the pollen parents of which contained either two B or zero B chromosomes. Through genetic and cytological analyses of these progenies and their parents we have identified that, while overall cytological estimates of chiasma frequencies were significantly lower in pollen mother cells with two B chromosomes as compared to zero B chromosomes, the recombination frequencies within some marker intervals were actually increased, particularly for marker intervals in lower recombination regions of chromosomes, i.e., pericentromeric regions. Thus, in perennial ryegrass, the presence of two B chromosomes redistributed patterns of meiotic recombination in pollen mother cells in ways which could increase the range of allelic variation available to plant breeders.